Przyjaźń u Nałkowskiej (na przykładzie powieści Narcyza, Hrabia Emil, Niedobra miłość) - Gajewska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article, while discussing the concept of friendship, presents social and personal relations between the protagonists of Zofia Nałkowska’s fiction. Against the background of tragic social conflicts, numerous shows of disloyalty, trade in women, low motives, and thoughtlessness, the writer points out to friendship as the only worthwhile relationship, even if it brings many disappointments. Apart from her enormous sensitivity to women’s plight, and focus on their mutual solidarity, Nałkowska often focused on friendship between men, representing their emotional engagement and delight of one man in another. In Nałkowska’s fiction, friendship is linked to risk, opening up to otherness, and internalization of the gaze of another human being. Friendly relationships, although they are fleeting and full of ethical tensions, help people to free themselves from their mould, change their character, and escape from dependencies that discipline their desires. Thus, friendship means a personality crisis, weakening of character, and temporary transgression. The passage, a temporary escape from entrenched ways of living, is possible in Nałkowska’s fiction only at the cost of a friendly bond.